Maslahah Sebagai Kerangka Berfikir Dan Tujuan Hukum Islam - Ririn Fauziyah; Agus Sholahudin Shidiq; Burhanatut Dyana (HKI IAI Miftahul Ulum Pamekasan, 2021)
Islamic law came with the realization of the mission and the maximization maslahah and elimination and minimization madarrah. In fact, there are frequently used the slogan,